Assessing the impact of the stability training on fitness rated with the Functional Movement Screen Test in a group of professional football players - Kołodziej, Gabriela; Kołodziej, Krzysztof (Wydawnictwo Uniwersytetu Rzeszowskiego, 2016)
Introduction: Football is a dynamic, ever-growing team sport. It’s fast action and spectacular character give this sport the title of the most popular in the world. However, due to its specificity it is related with a high risk of injury. An important element of injury prevention is comprehensive functional assessment of the player. The Functional Movement Screen Test is used as a tool to assess the risk of injury and basic movement patterns to determine the occurrence of disorders within the musculoskeletal system. Objective: The aim of the study is to compare the level of functional performance of football players who have stability exercises in their daily training sessions and of the players without such training. Material and Methods: The study was conducted in Rzeszow and the surrounding area on a group of 120 players. The functional assessment was performed using FMS test. Results: In the study group of players high level of functionality was observed. However, in the control group a series of tests showed an asymmetry and irregularities in the basic movement patterns. Conclusions: The study gave answers to the research questions.

Wstęp: Piłka nożna jest dynamicznym, ciągle rozwijającym się sportem drużynowym. Szybka akcja oraz widowiskowy charakter powodują, że jest to dyscyplina najbardziej popularna na świecie. Jednak ze względu na swoją specyfikę sport ten związany jest z dużym ryzykiem występowania urazów i kontuzji. Istotnym elementem profilaktyki przeciwurazowej jest kompleksowa funkcjonalna ocena zawodnika. Do tego celu służy The Functional Movement Screen Test, używany jako narzędzie screeningowe do oceny ryzyka występowania kontuzji oraz podstawowych wzorców ruchowych, aby stwierdzić występowanie zaburzeń w obrębie aparatu ruchu. Cel pracy: Celem pracy jest porównanie poziomu sprawności funkcjonalnej zawodników, u których w codziennym treningu są wprowadzone ćwiczenia o charakterze stabilizacyjnym w porównaniu z zawodnikami bez treningu. Materiał i metody: Badania przeprowadzono na terenie województwa podkarpackiego w grupie 120 piłkarzy. Ocenę funkcjonalną wykonano za pomocą testu FMS. Wyniki: U zawodników z grupy badanej zaobserwowano wysoki poziom sprawności funkcjonalnej. Jednak w grupie kontrolnej wykonywane testy wykazywały szereg asymetrii i nieprawidłowości w podstawowych wzorcach ruchowych.
Ocena wpływu treningu stabilizacyjnego na sprawność ocenianą testem Functional Movement Screen Test w grupie zawodników grających w piłkę nożną
Keywords: football; functional rate; the FMS Test; piłka nożna; ocena funkcjonalna; test FMS